Cadre Knowledge Level about Poedji Rochjati Score Card Against Implemention of Kspr Scoring for Pregnant Women - Erma Retnaningtyas (Institute of Computer Science (IOCS), 2022)
The cadre's lack of understanding about KSPR is an obstacle to collaboration between midwives and cadres in carrying out early detection of pregnant women. The purpose of this study was to analyze the level of knowledge of cadres about the Poedji Rochjati score card on the implementation of KSPR scoring on pregnant women in Jatisari Geger Village, Madiun. The research design used a cross sectional analytic survey. The population of all cadres in Jatisari Geger Village is 35 people, with a sample of 33 cadres. Sampling with simple random sampling technique with chi square test. SPSS output, at the 95% confidence level (α=0.05), p-value or Sig. (2-tailed) in the chi square table is 0.000, this number is smaller than =0.05 (0.000 0.05) which means that there is a relationship between knowledge and the implementation of KSPR for cadres in Jatisari Village, Geger District, Madiun Regency. Lack of knowledge of cadres about KSPR causes cadres to be less able to implement KSPR properly. There is a need for training on KSPR for cadres provided by midwives in order to increase the collaboration between midwives and cadres in implementing KSPR.